2021
DOI: 10.3390/molecules26175196
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Selected Natural Biomolecules in Sperm Production and Functionality

Abstract: Emerging evidence from in vivo as well as in vitro studies indicates that natural biomolecules may play important roles in the prevention or management of a wide array of chronic diseases. Furthermore, the use of natural compounds in the treatment of male sub- or infertility has been proposed as a potential alternative to conventional therapeutic options. As such, we aimed to evaluate the effects of selected natural biomolecules on the sperm production, structural integrity, and functional activity. At the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 254 publications
(433 reference statements)
0
27
0
Order By: Relevance
“…Infertility is a disease of the male or female reproductive system characterised by the inability to accomplish a pregnancy following at least 12 months of regular unprotected sexual intercourse [ 341 , 342 , 343 ]. According to statistics, 48 million couples and 186 million individuals live with infertility globally [ 341 ], and male factors account for at least 50% of all infertility cases worldwide [ 343 ].…”
Section: Health Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Infertility is a disease of the male or female reproductive system characterised by the inability to accomplish a pregnancy following at least 12 months of regular unprotected sexual intercourse [ 341 , 342 , 343 ]. According to statistics, 48 million couples and 186 million individuals live with infertility globally [ 341 ], and male factors account for at least 50% of all infertility cases worldwide [ 343 ].…”
Section: Health Effectsmentioning
confidence: 99%
“…Infertility is a disease of the male or female reproductive system characterised by the inability to accomplish a pregnancy following at least 12 months of regular unprotected sexual intercourse [ 341 , 342 , 343 ]. According to statistics, 48 million couples and 186 million individuals live with infertility globally [ 341 ], and male factors account for at least 50% of all infertility cases worldwide [ 343 ]. Oxidative stress (OS), which arises from an imbalance between ROS and protective antioxidants, can affect the entire reproductive lifespan of men and women [ 344 ] and has been shown to be a major cause of reproductive dysfunction [ 344 , 345 ].…”
Section: Health Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that common oral antioxidants (e.g., vitamin C, vitamin E, vitamin D, selenium, folate, zine, and carnitine) improve sperm quality (i.e., sperm count, motility, and morphology) both in men and in animal models reviewed by [168,169]. However, these studies have been focused on infertility-related sperm characteristics in young, rather than older, men.…”
Section: Common Antioxidant Compoundsmentioning
confidence: 99%